Understanding creativity in East Asia: insights from Confucius' concept of junzi. Issue 1 (2nd January 2016) - Tan, Charlene
Abstract : Research shows that East Asians generally value creativity when it brings about evolutionary changes and promotes moral and social values. With an aim to further understand the concept and cultural foundation of creativity in East Asia, this article focuses on Confucius' concept of junzi (exemplary or paradigmatic person). It is argued that a junzi embodies creativity in three main ways. First, a junzi exercises creativity by actively interpreting experiences and constructing personal meanings within one's sociocultural context. Second, a junzi 's creativity is grounded in and motivated by one's moral duty to achieve humanity and social harmony. Third, a junzi manifests creativity by bringing about an intermediate rather than radical domain change in society. The article concludes with the key implications of an East Asian concept of creativity for design creativity and innovation.